2018
DOI: 10.1108/pm-03-2017-0016
|View full text |Cite
|
Sign up to set email alerts
|

Users’ preference for green features in office properties

Abstract: Purpose The purpose of this paper is to examine the preference of office property users for green features in Lagos, Nigeria. This is with a view to determining the degree of users’ aspiration for green buildings in the country. Design/methodology/approach The study purposively sampled two office properties from the management portfolio of 88 registered estate firms in Lagos. Data were collected using self-administered questionnaire on two users purposively selected from each of the properties. The data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 14 publications
2
25
0
Order By: Relevance
“…In summary, the finding of this study showed that tenants were more favourably disposed and willing to pay for green features that confer comforts to occupants rather than those that confer benefits to the environment. This finding is not unexpected and in line with the outcomes of the earlier studies (Komolafe and Oyewole, 2015;Oyewole and Komolafe, 2018) on the preference of users for green features. The implication of this is that the tenants were more inclined to pay for features that confer occupants comforts such as 'Availability of contingency plans for power failure', 'Water saving toilet and baths facilities', 'Access to public transport within reasonable time', and 'Location of air intakes far from sources of pollution', it is recommended that tenants should be educated on the importance of features that are eco-friendly in order to enhance the sustainability of built environment.…”
Section: Tenants' Willingness To Pay For Green Featuressupporting
confidence: 91%
See 4 more Smart Citations
“…In summary, the finding of this study showed that tenants were more favourably disposed and willing to pay for green features that confer comforts to occupants rather than those that confer benefits to the environment. This finding is not unexpected and in line with the outcomes of the earlier studies (Komolafe and Oyewole, 2015;Oyewole and Komolafe, 2018) on the preference of users for green features. The implication of this is that the tenants were more inclined to pay for features that confer occupants comforts such as 'Availability of contingency plans for power failure', 'Water saving toilet and baths facilities', 'Access to public transport within reasonable time', and 'Location of air intakes far from sources of pollution', it is recommended that tenants should be educated on the importance of features that are eco-friendly in order to enhance the sustainability of built environment.…”
Section: Tenants' Willingness To Pay For Green Featuressupporting
confidence: 91%
“…The study also revealed that the features that ranked first and second in terms of TWTPI are 'energy conservation' with TWTPI of 3.12 and 'water, rain water and sewage' with TWTPI of 2.72 respectively. This finding is in line with Oyewole and Komolafe (2018) that property users in the study area were confronted with severe difficulty in the area of power and water supply.…”
Section: Tenants' Willingness To Pay For Green Featuressupporting
confidence: 91%
See 3 more Smart Citations